Gambaran Pola Pengobatan Antipsikotik pada Pasien Skizofrenia yang Mengalami Efek Samping Ekstrapiramidal di RSJD Atma Husada Mahakam Samarinda: Description of Antipsychotic Treatment Patterns in Schizophrenia Patients Experiencing Extrapyramidal Side Effects at Atma Husada Mahakam Mental Hospital, Samarinda - Fatwa, Nur; Fikriah, Ika; Abdullah, Yenny (Jurnal Medika : Karya Ilmiah Kesehatan, 2025)
Schizophrenia is a chronic mental disorder with a combination of psychotic symptoms such as hallucinations, delusions, motivational and cognitive dysfunction. Effective pharmacological therapy for treating schizophrenia is antipsychotic drugs. Side effects from the use of antipsychotic drugs can affect medication adherence in schizophrenia patients. Non-compliance with taking medication can result in a higher risk of recurrence rates. This study aims to determine the pattern of antipsychotic treatment in schizophrenic patients who experience extrapyramidal syndrome at RSJD Atma Husada Mahakam Samarinda. The research design used in this research is descriptive observational. The research data came from medical records of schizophrenia patients at RSJD Atma Husada Mahakam Samarinda for the inpatient period January 2022October 2023 using a purposive sampling method. A total of 86 samples were obtained consisting of 43 schizophrenia patients with extrapyramidal syndrome and 43 schizophrenia patients who did not experience extrapyramidal syndrome. The results of the study showed that the most common pattern of antipsychotic treatment in EPS patients was polytherapy treatment (69.8%).